2022
DOI: 10.1192/j.eurpsy.2022.26
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged impact of the COVID-19 pandemic on self-harm hospitalizations in France: A nationwide retrospective observational study

Abstract: Background The first wave of the COVID-19 pandemic in France was associated with a reduced number of hospitalizations for self-harm, with the exception of older people. The on-going pandemic may have both sustained and delayed effects. Methods Data were extracted from the French national hospital database (PMSI), a nationwide exhaustive database. The number of self-harm hospitalizations (ICD-10 codes X60–84) between September 1, 2020 and August 31, 2021 (N = 85,679) was compared to 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…Then, a substantial increase was observed from November 2020 that continued until the end of the study period more than 18 months later. Again, this increase is very similar to which was observed for self-harm hospitalizations [ 19 ]. Therefore, two phases can be identified during the pandemic: a decrease during the first months continuing historical trends, and an increase since the end on 2020.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Then, a substantial increase was observed from November 2020 that continued until the end of the study period more than 18 months later. Again, this increase is very similar to which was observed for self-harm hospitalizations [ 19 ]. Therefore, two phases can be identified during the pandemic: a decrease during the first months continuing historical trends, and an increase since the end on 2020.…”
Section: Discussionsupporting
confidence: 85%
“…Following this early period, warning signs have been reported by clinicians about a possible increase in the number of mental health consultations among children [ 23 ]. Self-harm hospitalizations for the period September 2020-August 2021 showed a persistent decrease in middle-aged people but an important increase in female adolescents from January 2021 [ 19 ]. The prolonged effects of COVID-19 on suicide attempts need to be further examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent work from our team has underlined the challenge of drawing firm conclusions Table 2 Rate ratios for the dispensing of the three psychotropic drug categories between January 1, 2019, and April 30, 2021, among French military personnel, considering that the epidemic breakpoint date was January 24, 2020 *** p < 0.001; ** p < 0.01; * p < 0.05 a Measured in weeks from 24th January 2020 to April 2021 (from week 1 to 124) b Coded 1 from the start of the epidemic, defined at 24th January 2020, 0 otherwise c Measured in weeks, coded 0 before the start of the epidemic and equal to the number of weeks afterwards (from week 1 to 67) about the overall effects of the epidemic. For instance, our analysis of suicide attempts in the general population in France indicated that there was a decrease in selfharm hospitalizations both during the first lockdown [28] and during the second stage of the COVID-19 pandemic [29], except among teenage girls. It is therefore essential to take into account the specificities of the study population, and healthy young individuals from the general active population should be studied specifically before extrapolating our results.…”
Section: Discussionmentioning
confidence: 96%
“…Other recent work from our team has underlined the challenge of drawing firm conclusions about the overall effects of the epidemic. For instance, our analysis of suicide attempts in the general population in France indicated that there was a decrease in self-harm hospitalizations both during the first lockdown [ 28 ] and during the second stage of the COVID-19 pandemic [ 29 ], except among teenage girls. It is therefore essential to take into account the specificities of the study population, and healthy young individuals from the general active population should be studied specifically before extrapolating our results.…”
Section: Discussionmentioning
confidence: 99%